Interim fluorine-18 fluorodeoxyglucose PET-computed tomography and cell of origin by immunohistochemistry predicts progression-free and overall survival in diffuse large B-cell lymphoma patients in the rituximab era. Issue 10 (October 2016) - de Oliveira Costa, Renata; Hallack Neto, Abrahão; Siqueira, Sheila; Lage, Luis Alberto de Padua Covas; de Paula, Henrique M.; Coutinho, Arthur M.; Pereira, Juliana
Abstract : Objective: The aim of this study was to analyze the prognostic value of the interim PET (iPET)-computed tomography (CT) (iPET-CT) after two cycles of immunochemotherapy with the R-CHOP protocol in patients with diffuse large B-cell non-Hodgkin lymphoma (DLBCL) treated with a curative intent in combination with the neoplastic cell origin defined by Hans's immunohistochemstry algorithm followed in a reference center for cancer treatment in Brazil. Materials and methods: We prospectively evaluated 147 DLBCL patients treated with R-CHOP-21 to assess the value of the International Prognostic Index, iPET-CT, and cell of origin by immunohistochemistry as prognostic markers in the rituximab era. Fluorine-18 fluorodeoxyglucose PET-CT was performed after two cycles (iPET-CT) and at the end of treatment in 111 patients. Lymphoma cases were categorized into germinal center (GC) and nongerminal center subtypes by immunohistochemistry according to Hans's algorithm. Results: The median age of GC-DLBCL patients (52.7 years) was lower than that of nongerminal center-DLBCL patients (59.4 years) ( P =0.021); in addition, it was lower in patients with negative iPET-CT findings (52.7 years) versus positive findings (59.4 years) ( P =0.031). The overall survival at 48 months was 100% for iPET-CT-negative GC-DLBCL patients and 61.2% for iPET-CT-positive GC-DLBCL patients ( P =0.002). Progression-free survival at 30 months was 100% for iPET-CT-negative GC-DLBCL patients and 60.3% for iPET-CT-positive GC-DLBCL patients ( P =0.001). Conclusion: We conclude that iPET-CT associated with cell origin identified a very good prognostic group in DLBCL patients treated with R-CHOP. Video Abstract:http://links.lww.com/NMC/A59 Abstract : Supplemental Digital Content is available in the text.